Safety and performance of the Vienna self-expandable transcatheter aortic valve system: 6-month results of the VIVA first-in-human feasibility study - Briedis, Kasparas; Mizariene, Vaida; Rumbinaite, Egle; Jurenas, Martynas; Aldujeli, Ali; Briede, Kamilija; Jakuska, Povilas; Jankauskas, Antanas; Ceponiene, Indre; Lenkutis, Tadas; Zaliunas, Remigijus; Benetis, Rimantas (Frontiers in Cardiovascular Medicine, 2023)
Background. The novel Vienna TAVI system is repositionable and retrievable, already pre-mounted on the delivery system, eliminating the need for assembly and crimping of the device prior to valve implantation. Aims. The purpose of this first-in-human feasibility study was to determine the safety, feasibility, clinical and hemodynamic performance of the Vienna TAVI system at 6-month follow-up. (ClinicalTrials.gov identifier NCT04861805). Methods. This is a prospective, non-randomized, single-arm, single-center, first-stage FIH feasibility study, which is followed by a second-stage pivotal, multicenter, multinational study in symptomatic patients with severe aortic stenosis (SAS). The first-stage FIH study evaluated the safety and feasibility, clinical and hemodynamic performance of the device in 10 patients with SAS based on recommendations by the VARC-2. Results. All patients were alive at 3-month follow-up. 1 non-cardiovascular mortality was reported 5 months after implantation. There were no new cerebrovascular events, life-threatening bleeding or conduction disturbances observed at 6-month follow-up. The mean AV gradient significantly decreased from 48.7±10.8 to 7.32±2.0 mmHg and mean AVA increased from 0.75±0.18 to 2.16±0.42 cm2 (p<0.00001). There was no incidence of moderate or severe total AR observed. In the QoL questionnaires, the patients reported a significant improvement from the baseline 12-KCCQ mean score 58±15 to 76±20. NYHA functional class improved in two patients, remained unchanged in one patient. There was an increase in mean 6-min-walk distance from baseline 285±97 to 347±57 meters. Conclusions. This study demonstrates that using Vienna TAVI system has favourable and sustained 6-month safety and performance outcomes in patients with symptomatic severe aortic stenosis.